Revisiting Redundant Text Color Coding in User Interfaces - Sandvold, Fredrik Strømsvåg; Schuller, Thomas; Rolfsvåg, Andreas; Sikkerbøl, Knut-Erik; Medola, Fausto Orsi [UNESP]; Sandnes, Frode Eika (Springer Nature, 2023)
Practices for using redundant text color in user interfaces vary. Some designers have carefully incorporated redundant coding in their design, while in other instances redundant coding is not utilized. There is a vast body of research on the effects of color on visual search. In this study we wanted to corroborate earlier findings in the current context. A simple recognition experiment was configured. The results agreed with the literature in that color has a significant effect on response time when the color is known, while it has no effect on recall. The results support the use of redundant color coding in interfaces, especially for time-critical applications where the user must act rapidly.
Keywords: redundant color coding; text color; user interface